Children's views about factors affecting access to home, school and community play. Issue 4 (1st October 2020) - Finney, Rebecca; Atkinson, Cathy
ABSTRACT: Despite Article 31 of the United Nations Convention on the Rights of the Child, there are continuing concerns around children's access to play and limited focus on gaining children's views about this. This systematic literature review examined children's views on factors affecting their access to play at home, school and in the community. Eleven studies met the inclusion criteria and were assessed using qualitative and quantitative frameworks. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) framework was used, and nine studies were included in the final synthesis. Analysis looked at children's views in relation to temporal, spatial and psychological factors affecting play access, but found there was significant overlap between the domains. Factors were then explored further from a social and ecological perspective. Two conceptual models were developed from the findings, which may help practitioners understand factors affecting play access. Implications for future research and practice were considered.